Juridical Analysis: Online Single Submission (OSS) System for Dynamic Risk-Based Business Licensing - Wiranti, Wiranti (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2023)
This comprehensive study examines the dynamics of business licensing policies and the adoption of the Online Single Submission (OSS) system as a risk-based solution in public services. The research assesses the legal aspects of business licensing policies, particularly focusing on the OSS system, and evaluates its impact on the efficiency and effectiveness of public services. Employing a juridical approach, the study conducts thorough legal analysis of relevant legislation, regulations, and judicial precedents. Empirical data from case studies and stakeholder interviews in OSS system implementation are collected and analyzed. The findings emphasize the OSS system’s importance in streamlining licensing procedures and reducing administrative burdens. Through a risk-based approach, the OSS system promotes transparency, accountability, and fairness while enhancing legal certainty and minimizing corruption risks. The study also identifies challenges, such as data privacy and cybersecurity concerns, and potential conflicts in decision-making processes. Addressing these challenges will improve the effectiveness and sustainability of the OSS system. The research contributes to public administration and legal studies, providing valuable insights for policymakers and legislators in designing and refining business licensing policies and implementing the OSS system. Ultimately, the study aims to promote good governance, facilitate economic growth, and enhance the quality of public services.